Essentials of contemporary advertising - Arens, William F. (McGraw - Hill, 2007)
Essentials of Contemporary Advertising, 1/e by William Arens and David Schaefer explores the core principles that drive advertising, using a lively voice that goes beyond academic theory. The authors’ goal was to present advertising as it is actually practiced and make the fundamentals accessible and relevant to the student’s “real life.” This approach truly transcends the conceptual and propels students into an exciting and practical dimension.